Climate change influence in occupational exposure to chemical substances - Viegas, Susana (2021)
The climate change impact on occupational health and safety has not been a target for many considerations and deep analysis. However, workers can be affected directly and indirectly by climate change since an increase in temperature in the workplace or a change in the composition of a raw material that needs to be handle by workers can imply an increase in exposure to a specific chemical substance. An extensive search was performed to identify scientific papers available in PubMed published after 2010, discussing the influence that climate change can have on occupational exposure to chemicals. Of the 34 papers found and evaluated in total, 28 were excluded from the present review because they did not fulfill the inclusion criteria and only 6 papers were considered for further analysis. Pesticides, natural toxins, such as mycotoxins, polycyclic aromatic hydrocarbons, particles, and other toxic compounds related to fire fumes were mentioned in the papers analyzed. Considering the lack of studies found and the emergency of a climate change scenario is possible to conclude that research work focused on specific chemical substances and occupational settings should be developed to guarantee a more accurate risk assessment related to the influence of climate change in occupational exposure.